1988
DOI: 10.2151/jmsj1965.66.4_515
|View full text |Cite
|
Sign up to set email alerts
|

A Numerical Experiment on Sea Surface Temperature Anomalies and Warm Winter in Japan

Akio Kitoh

Abstract: Impact of the sea surface temperature anomalies (SSTAs) on atmospheric circulations are studied with emphasis on the winter climate in Japan with the use of an atmospheric general circulation model.The empirical orthogonal function analyses are performed for precipitation, geopotential height at 500mb and surface air temperature. It is shown that leading eigenvectors of precipitation are zonally elongated in the tropics and that the distribution of positive and negative precipitation anomalies is dependent on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…2d). So it may be possible that higher SSTs over the central equatorial Pacific region can produce more WP-type circulations in the extratropics (Kitoh, 1988a). However, when compared with Fig.…”
Section: Composite Analysismentioning
confidence: 90%
“…2d). So it may be possible that higher SSTs over the central equatorial Pacific region can produce more WP-type circulations in the extratropics (Kitoh, 1988a). However, when compared with Fig.…”
Section: Composite Analysismentioning
confidence: 90%
“…Orography as well as SST anomalies must play an important role in such a zonal/eddy relationship. Kitoh (1988) performed ten 180-day runs with the MRI•GCM under perpetual January conditions and obtained a circulation pattern relevant to a warm winter in Japan for run AW (the composited SST when Japan experienced warm winters) or for run A7 (positive SSTA over the equator east of the dateline), but not for run AS (very close to A7, but positive SSTA south of the equator on the dateline).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…The winter climate in Japan tends to be mild during El Nino years, but there have been exceptions, such as the 1976/77 winter. Kitoh (1988) performed a GCM experiment to study the impact of SST anomalies on the resulting atmospheric circulation with emphasis on the winter climate in Japan. His results produced a northern mid-latitude circulation pattern which was closely related to the winter temperature in Japan and showed a possible role of the equatorial SST anomaly east of the dateline in inducing such a circulation pattern.…”
Section: ©1988 Meteorologicalmentioning
confidence: 99%
“…(2) Sea-surface temperature (SST) Monthly-mean SST, which is digitized on 2°*2° latitude-longitude grids over the whole globe, was obtained from the Climate Analysis Center (CAC) during 1970-1984and the Oceanographical Division in JMA during 1985-1988 (3) Sea-water temperature along 137°E…”
Section: Data Used In the Present Study (1) Temperature Over Japanmentioning
confidence: 99%
“…In East Asia, there exist three types of temperature anomaly distributions according to the fluctuation of a blocking ridge in the northeastern Pacific. Kitoh (1988) indicated that a positive SST anomaly over the equator east of the dateline gives the largest anticyclonic circulation response over the North Pacific Ocean and the warmest surface-air temperature anomalies in East Asia in winter. Iwasaka et al (1988) divided the North Pacific Ocean into four subdomains on the basis of similarity in temporal variations of the SST anomaly and showed the simultaneous relationship between winter monsoon strength and the SST of the subdomain around Japan.…”
Section: Introductionmentioning
confidence: 99%